مساهمة التفاؤل والمساندة الاجتماعية في التنبؤ بالاستجابة للعلاج الكيميائي لدى عينة من مرضى السرطان - كريبع خديجة بنت محمد; طعبي عائشة الهام; زعابطة سيرين هاجر (My University, 2022)
The current research aims to identify the contribution of optimism and social support in predicting the response to chemotherapy in cancer patients, as well as the level of optimism and support and investigating the relationship between them, as well as studying the differences in their averages according to social status, educational level and disease duration. The research sample amounted to 61 cancer patients who were intentionally selected from various departments specialized in the treatment of cancerous tumors during the time period from the beginning of March 2022 until May 2022. The descriptive approach was followed, and we relied on the optimism scale (orientation towards life) by Scheier& Carver (1985), which was Arabized by Badr Muhammad Al-Ansari, and the scale of social support (Sarson et al. Abu Bayh, 1990), and the medical form for estimating the response to chemotherapy as we relied on the statistical package for social sciences spss22. The research concluded with a set of the following results: 1. There is a high level of optimism among a sample of cancer patients. 2. There is a level of satisfaction with support among a sample of cancer patients. 3. Optimism is positively related to social support (satisfaction). 4. Optimism contributes to predicting response to chemotherapy in cancer patients. 5. Satisfaction with social support contributes to predicting response to chemotherapy in cancer patients. 6. There are statistically significant differences in satisfaction with support according to social status in favor of the widowed, the divorced. 7. There are no statistically significant differences in optimism according to social status. 8. There are statistically significant differences in optimism according to the educational level in favor of the lower level (primary, intermediate). 9. There are no statistically significant differences in satisfaction with support according to the educational level. 10. There are no statistically significant differences in optimism according to the duration of the disease. 11. There are no statistically significant differences in satisfaction with support according to the duration of the disease.
دراسة ميدانية على عينة من مرضى السرطان بمستشفيات الاغواط